PENGUATAN PENGATURAN HAK ANAK BERDASARKAN KONSTITUSI DAN PERBANDINGAN KONSTITUSI DIBERBAGAI NEGARA - Ismail Aris (AN-NISA, 2018)
This article shows that the constitution or the 1945 Constitution of the Republic of Indonesia can not be regarded as children's constitution which adopts the principles of child protection under the Convention on the Rights of the Child. It also shows that Indonesia is not serious about the theme of child protection discourse such as Ecuador, Egypt, Finland and South Africa in protecting, fulfilling and respecting and explicitly specifying the rights of children in its constitution. Based on the argument above, it is very urgent for Indonesia to do constitutionalism the rights of the child. Based on the principles that adopted by the convention on the right of the child as a solution as an effort to save and protect the rights of the child from negligence and neglect of the State to protect and fulfill the human rights and constitutional rights of the child. The effort of constitutionalism is also considered as a strengthening effort in the formation of legislation in the future as well as the basis or test stone of the Constitutional Court in handling the future judicial review of the Law which violates the norm on the protection of children's rights under the Constitution. In addition, it is urgent for constitutionalism and incorporates the idea of constitutional complaints in the Constitutional Court through the Constitution. Thus, as a basis for constitutional protection of the child if the State has neglect to protect the human rights and constitutional rights of the child by conducting constitutional complaint in the Constitutional Court, in order for the State to fulfill its constitutional obligations which have been regulated under the constitution.